Co-creation of staff training to address health-related social needs in emergencies - Linda Highfield; Gayla Ferguson (Frontiers in Public Health)
BackgroundHealth-related social needs (HRSN), such as housing and transportation barriers, contribute to poor health outcomes and increased healthcare costs. Patient navigators help connect patients to community resources, but workforce training gaps are a challenge. The Strengthening Peer AHC Navigation (SPAN) study aimed to enhance navigation training during the COVID-19 Public Health Emergency.MethodsUsing a stakeholder-driven peer planning approach, SPAN co-developed a quality improvement plan for patient navigation training. Training focused on housing and transportation navigation and included didactic sessions, hands-on case studies, and biweekly expert consultations. Self-efficacy surveys measured navigator confidence pre- and post-training, and changes in navigation case resolution rates were assessed.ResultsSeventeen navigators participated in training. Self-efficacy scores improved, particularly in housing and transportation navigation. Resolved navigation cases increased by 29% (p = 0.001) over 6 months post-training. Participants reported increased confidence, knowledge, and empathy for patients with HRSN.ConclusionThe SPAN peer planning model successfully developed and implemented an adaptive navigation training program, improving navigator confidence and patient outcomes. Findings highlight the value of stakeholder-driven training and ongoing expert support in strengthening the social needs workforce. Further research should explore sustainable models for workforce development in healthcare settings.